Endowment fund lease in Iraqi law An analytical study - payam kareem (الرافدین للحقوق, 2023)
There are many legislations regarding the regulation of endowment funds in general and the endowment lease in particular. As the provisions regulating the lease of endowment money is scattered in several laws and regulations. With the multiplicity of legislations regulating this field, the rules that apply to leasing endowment funds are numerous and vary according to the type of endowment money. The provisions of the legislation regulating the provisions of the endowment funds in Iraq differ from those in effect in the Kurdistan Region. Thus, given that some Iraqi legislations have not been enforced in the region, in addition to the difference in the authority supervising the endowment funds, as there is no Ministry of Endowments in Iraq, and the bureaus have been dissolved to replace it. On the other hand, there is the Ministry of Endowments and Religious Affairs in the Kurdistan Region-Iraq. One of the most important conclusions of this study is that it is necessary to distinguish between the types of endowment in order to clarify the legal adaptation of endowment funds. The charitable endowment is irreversible, and it is an overthrow of the property. However, this cannot be generalized to all types of endowments that exist in the Iraqi Law. In light of the explicitness of what was stated in the decree law permissibility of liquidating the offspring endowment, which allows any eligible mercenary or one of his eligible heirs to request the liquidation of the offspring or joint endowment, whether it has been established before or after the decree goes into effect. Hence, the offspring endowment is reversible, and cannot be said that it is an overthrow of the property. The joint endowment also has a dual nature, as it is considered reversible with regard to what was endowed on the offspring, given the possibility of its liquidation, and it is irreversible with regard to the share belonging to the charitable body. The study presented some suggestions in a relevant context to the subject of the study.